2013
DOI: 10.3109/19401736.2013.814108
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny ofTrachylepissp. (Reptilia) from Turkey inferred from mtDNA sequences

Abstract: The taxonomic status of the species included into the genus Trachylepis in Turkey are doubtful. So far, three morphological species have been attributed to this genus in Turkey; Trachylepis aurata. T. vittata, and T. septemtaeniata. Here, we investigated the taxonomy of the Turkish Trachylepis species by employing phylogenetic and phylogeographic approaches and using mitochondrial DNA (cytochrome b and 12 S rRNA). In total, 45 Trachylepis and 6 Mabuya specimens were used analyzed. Phylogenetic analyses were ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Longitidunal rows of small spots on the dorsum is also a colour-pattern characteristics of Heremites septemtaeniatus (Moravec et al 2006); however, the reliability of the contact position of third supraocular and frontal as a distinctive character between H. auratus and H. septemtaeniatus and the occurrence of H. septemtaeniatus in Turkey was considered doubtful by Durmuş et al (2011). Although taxonomic reorganization is still needed for the aforementioned taxa (Güçlü et al 2014), it is considered that the sample in the present study resembles H. a. transcaucasicus, which is not mentioned from Turkey in the previous literature (Moravec et al 2006;Durmuş et al 2011;Güçlü et al 2014). Since any additional specimens from the site could not be found, the morphological variation could not be assessed.…”
Section: Discussionmentioning
confidence: 84%
“…Longitidunal rows of small spots on the dorsum is also a colour-pattern characteristics of Heremites septemtaeniatus (Moravec et al 2006); however, the reliability of the contact position of third supraocular and frontal as a distinctive character between H. auratus and H. septemtaeniatus and the occurrence of H. septemtaeniatus in Turkey was considered doubtful by Durmuş et al (2011). Although taxonomic reorganization is still needed for the aforementioned taxa (Güçlü et al 2014), it is considered that the sample in the present study resembles H. a. transcaucasicus, which is not mentioned from Turkey in the previous literature (Moravec et al 2006;Durmuş et al 2011;Güçlü et al 2014). Since any additional specimens from the site could not be found, the morphological variation could not be assessed.…”
Section: Discussionmentioning
confidence: 84%
“…Based on Güçlü et al . (2014), the three Turkish species Heremites auratus , H. vittatus and H. septemtaeniatus are monophyletic, and these authors suggested that the H. vittatus lineage split first, in the late Miocene (10.54 Ma). The other two species ( H. septemtaeniatus and H. auratus ) seem to diverge at the end of the Messinian Salinity Crisis (5.27 Ma).…”
Section: Discussionmentioning
confidence: 99%
“…(2013) for skink and cordyliform relationships, and on Güçlü et al . (2014) and Karin et al . (2016) for Mabuyidae relationships.…”
Section: Methodsmentioning
confidence: 96%
“…Data on new locality, osteology, and phylogenetic of H. vittatus exist in the literature (Güçlü et al, 2014;Rastergar-Pouyani et al, 2013;Kumlutaş et al, 2015). However, there is limited data about life-history such as age structure, growth pattern, or longevity of H. vittatus (Kalaycı et al, 2018).…”
Section: Introductionmentioning
confidence: 99%